The perception of patients in relation to the quality of care and assistance received in hospital institutions: integrative literature review (Research, Society and Development, 2022)
This project aims to understand the patient's experience and his perception of the quality of care related to health services during the period of hospitalization and the unveiling of the educational role of professionals during the service delivery process. Methodology: It is characterized as an Integrative Literature Review. Results: After all the methodological procedure, the search resulted in a total of 7193 articles. Of these, 94 were found in the LILACS database, 2559 in the MEDLINE platform, 4527 in PUBMED and 13 in SCIELO. Of these, after applying the inclusion criteria to integrate this study, a total of 7189 were not in accordance with the eligibility criteria and were excluded, leaving only 04 satisfactory samples. Conclusion: The present study brought within it aspects of professional qualification for the provision of quality and safe health services, in addition to highlighting the perspective of patients as a destination related to receiving care in a situation of hospitalization in hospital institutions. Thus, the objective of this study was satisfactorily achieved, however, despite having gained important information about the educational role of professionals, it left something to be desired regarding the analysis of this role in the hospital environment due to the lack of adequate samples to compose the study.